Experimental multi-scale approach to determine the local mechanical properties of foam base material in polyisocyanurate metal panels. (January 2021) - Gahlen, P.; Fröbel, S.; Karbach, A.; Gabriel, D.; Stommel, M.
Abstract: Polyisocyanurate (PIR) foams were examined regarding their local chemical composition using ATR-IR spectroscopy. As a special parameter the PIR: Amide III intensity ratio is to be mentioned, which represents the quantity of the formed PIR groups. Based on the local PIR: Amide III intensity ratio, the mechanical properties (Young's modulus) of the foam base material were analyzed at defined positions by AFM and Nanoindentation. It turned out that the AFM method is only suitable for qualitative analysis, because the values differ strongly from macroscopic measurements. For the measurements using nanoindentation, a new embedding method was developed, which achieves significantly more realistic and reproducible results compared to the embedding method used in the literature and shows a very good agreement with the macroscopic values. In general, it has been shown that a higher PIR: Amide III intensity ratio tends to lead to a higher Young's modulus. Nevertheless, there are other, currently unknown characteristic values which also influence the Young's modulus. Highlights: Relationship between the local chemical composition and mechanical properties of the polyisocyanurate foam base material. Development of a new method for the analysis of the mechanical properties of the foam base material using nanoindentation. Comparison of nano-/micro-scale and macro-scale measurements methods.